BIOMECHANICAL RESEARCH OF ROD SYSTEM AT MODELING OSTEOSYNTHESIS OF TIBIAL PLATEAU FRACTURE - Babalyan, V.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The article is reported about results of biomechanical research of rod system forosteosynthesis of tibial plateau fracture. Experimental part was held on wood models and pig’s tibia. It is found out, that rod system providesmuch less load for tibial plateau. Kneejointtakesonly 40-50% ofexternalload.